Impact of acellular hemoglobin‐based oxygen carriers on brain apoptosis in rats. Issue 8 (28th March 2014) - Vandegriff, Kim D.; Malavalli, Ashok; Lohman, Jeff; Young, Mark A.; Terraneo, Laura; Virgili, Eleonora; Bianciardi, Paola; Caretti, Anna; Samaja, Michele
<x xml:space="preserve">Abstract</x> Background Extracellular hemoglobin (Hb)‐based oxygen carriers (HBOCs) are under extensive consideration as oxygen therapeutics. Their effects on cellular mechanisms related to apoptosis are of particular interest, because the onset of proapoptotic pathways may give rise to tissue damage. Study Design and Methods The objective was to assess whether the properties of the Hb that replaces blood during an isovolemic hemodilution would modulate apoptotic‐response mechanisms in rat brain and whether such signaling favors cytoprotection or damage. We exposed rats to exchange transfusion (ET; 50% blood volume and isovolemic replacement with Hextend [negative colloid control], MP4OX [PEGylated HBOC with high oxygen affinity], and ααHb [αα‐cross‐linked HBOC with low oxygen affinity; n = 4‐6/group]). Sham rats acted as control. Animals were euthanized at 2, 6, and 12 hours after ET; brain tissue was harvested and processed for analysis. Results In MP4OX animals, the number of neurons that overexpressed the hypoxia‐inducible factor (HIF)‐1α was higher than in ααHb, particularly at the early time points. In addition, MP4OX was associated with greater phosphorylation of protein kinase B (Akt), a well‐known cytoprotective factor. Indeed, the degree of apoptosis, measured as terminal deoxynucleotidyl transferase–positive neurons and caspase‐3 cleavage, ranked in order of MP4OX < Hextend < ααHb. Conclusion Even though both HBOCs showed increased levels of HIF‐1α compared to shams or Hextend‐treated animals, differences in signaling events resulted in very different outcomes for the two HBOCs. ααHb‐treated brain tissue showed significant neuronal damage, measured as apoptosis. This was in stark contrast to the protection seen with MP4OX, apparently due to recruitment of Akt and neuronal specific HIF‐1α pathways.